Current state of medical waste management in an emerging city of Bangladesh - Sajjad Hossain Shozib; A.R.M. Towfiqul Islam; Masum A. Patwary; Mohammed A. Mamun; Md. Naimur Rahman; Kevin Lo (Green Technologies and Sustainability)
A rising concern of inappropriate medical waste management in developing countries like Bangladesh brings higher health risk problems specially during viral outbreak. In this study, we analyzed the medical waste management in the rapid urbanizing area of Rangpur City, northern Bangladesh. In all, 20 healthcare centers were used for collecting data, random stratified sampling and waste weighing methods. The statistical data analysis used for the purposes of the study was linear regression, Pearson’s correlation, and logistic regression. We find that Rangpur City generates around 3.22 tons (± 1.02 SD) of medical waste daily, among which about 20% is hazardous according to WHO classification standards. Hazardous waste varied markedly in amount and proportion between healthcare establishments of different size and type. The study reveals how healthcare waste is mismanaged in the city and offers important insights for policymakers to drive healthcare waste better the management practices.